Herpes simplex virus 1 induces egress channels through marginalized host chromatin - Myllys M; Ruokolainen V; Aho V; Smith EA; Hakanen S; Peri P; Salvetti A; Timonen J; Hukkanen V; Larabell CA; Vihinen-Ranta M (NATURE PUBLISHING GROUP, 2022)
Lytic infection with herpes simplex virus type 1 (HSV-1) induces profound modification of the cell nucleus including formation of a viral replication compartment and chromatin marginalization into the nuclear periphery. We used three-dimensional soft X-ray tomography, combined with cryogenic fluorescence, confocal and electron microscopy, to analyse the transformation of peripheral chromatin during HSV-1 infection. Our data showed an increased presence of low-density gaps in the marginalized chromatin at late infection. Advanced data analysis indicated the formation of virus-nucleocapsid-sized (or wider) channels extending through the compacted chromatin of the host. Importantly, confocal and electron microscopy analysis showed that these gaps frequently contained viral nucleocapsids. These results demonstrated that HSV-1 infection induces the formation of channels penetrating the compacted layer of cellular chromatin and allowing for the passage of progeny viruses to the nuclear envelope, their site of nuclear egress.